Maslahah dalam Vaksinasi: Analisis Fatwa Malaysia dan Indonesia: Maslahah in Vaccination: An Analysis of the Fatwa of Malaysia and Indonesia - Pauzi, Norhidayah; Man, Saadan (Jurnal Fiqh, 2017)
Vaccination is one of the preventative measures taken to prevent harmful life-threatening illnesses. However, today, more people are rejecting the vaccine based on mistaken information and wrong claims about the vaccine. Furthermore, different in status fatwas on the use of vaccines between Malaysia and Indonesia has added more concern for them on vaccination. This article analyzes, by comparison, the medical fatwa issued by the Malaysian Fatwa Committee and the Indonesian Ulama Council. Library and interview methods are used together to complement the study. The findings show that Malaysia permit the use of Meningitis vaccine based on the approach of akhaf al-dararayn and maslahah daruriyyah for the purpose of saving lives, in contrast to Indonesia that bans the use of Meningitis vaccine as it was found to have contact with impurified sources of pigs and there are other alternatives for halal vaccine.